Moderasi Beragama dan Polarisasi Digital: Respons terhadap Isu Keagamaan di Media Sosial Indonesia - M. Reza Fahrezi; Abdul Ghofar Saifudin (Moderasi : Journal of Islamic Studies, 2026)
This article examines the role of religious moderation in responding to netizen polarization over religious issues on Indonesian social media. Using a qualitative integrative literature review, the study synthesizes recent literature on religious moderation, digital polarization, filter bubbles, echo chambers, digital literacy, and religious communication. The findings indicate that religious polarization in social media emerges from the interaction of digital-religious literacy gaps, selective exposure, network homophily, platform recommendation systems, the shifting of religious authority to digital figures, and affective narratives that mobilize group identity. However, polarization should not be reduced to algorithms alone; it is also shaped by user behavior, social networks, political-religious identity, and the unequal circulation of moderate and confrontational narratives. Religious moderation provides a digital ethical framework grounded in tawazun, i'tidal, tasamuh, and tabayyun to encourage fair, proportional, empathetic, and non-confrontational responses. The article recommends strengthening moderate counter-narratives through creative content packaging, collaboration with credible digital actors, community-based religious literacy, and the integration of media and information literacy into religious education. This study contributes to contemporary Islamic studies by translating wasathiyyah into digital communication ethics for Indonesia’s plural society.